Congestion by accident? Traffic and accidents in England - Ilias-Nikiforos Pasidis (European Regional Science Association (ERSA), 2015)
The goal of this paper is the estimation of the effect of accidents on traffic congestion and vice versa. In order to do this, I use ?big data? of highway traffic and accidents in England for the period 2007-2013. The data exhibit some remarkably stable cyclical pattern of highway traffic which is used as a research setting that enables the identification of the causal effect of accidents on traffic congestion and vice versa. The estimation draws on panel data methods that have previously been used to analyse the bahaviour of electricity day-ahead mar- ket prices. A positive relationship between traffic congestion and road accidents would yield multiplicative benefits for policies that aim at reducing either of them. In addition, we will explore potential heterogeneous effects around different metropolitan areas and regions. This is one of the few studies that makes use of the increasing volume of big datasets, which are publicly available from governments and local authorities.
Keywords: R4; 330; accidents; traffic; congestion; highways; bigdata; panel; England